2022
DOI: 10.1111/cts.13263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP1A2 activity: Relationship between the endogenous urinary 6‐hydroxymelatonin to melatonin ratio and paraxanthine to caffeine ratio in dried blood spots

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Very recently, Magliocco et al reported that a method for phenotyping CYP1A2 from the ratio of urinary MEL to MEL metabolites, which could not be correlated with the CYP1A2 phenotyping method of the caffeine/paraxanthine concentration ratio in DBS. 22) The reason for this may involve the influence of fluctuations in MEL renal clearance. Here, the CL m(MEL) formula can be converted as follows (X MEL : urinary MEL excretion) 8) :…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Magliocco et al reported that a method for phenotyping CYP1A2 from the ratio of urinary MEL to MEL metabolites, which could not be correlated with the CYP1A2 phenotyping method of the caffeine/paraxanthine concentration ratio in DBS. 22) The reason for this may involve the influence of fluctuations in MEL renal clearance. Here, the CL m(MEL) formula can be converted as follows (X MEL : urinary MEL excretion) 8) :…”
Section: Discussionmentioning
confidence: 99%